Before I Go To Sleep - Watson, S. J. (Australia Text Publishing Melbourne, 2014)
An amnesiac attempts to reconstruct her past by keeping a journal and discovers the dangerous inconsistencies in the stories of her husband and her secret doctor.
Keywords: Memory disorders -- Women authors -- Life change events -- Amnesiacs -- Memory